Composition, host responses and clinical applications of bioadhesives. Issue 12 (24th June 2022) - Dhandapani, Vignesh; Ringuette, Vickie; Desrochers, Monika; Sirois, Marco; Vermette, Patrick
Abstract: Bioadhesives are medical devices used to join or seal tissues that have been injured or incised. They have been classified into tissue adhesives, sealants, and hemostatic agents. Bioadhesives such as FloSeal®, CoSeal®, BioGlue®, Evicel®, Tisseel®, Progel™ PALS, and TissuGlu® have been commercialized and used in clinical setting. They can be formulated with natural or synthetic components or a combination of both including albumin, glutaraldehyde, chitosan, cyanoacrylate, fibrin and thrombin, gelatin, polyethylene glycol (PEG), along with urethanes. Each formulation has intrinsic properties and has been developed and validated for a specific application. This review article briefs the mechanisms by which bioadhesives forms adhesion to tissues and highlights the correlation between bioadhesives composition and their potential host responses. Furthermore, clinical applications of bioadhesives and their application‐driven requirements are outlined.